2017
DOI: 10.4103/ijri.ijri_294_16
|View full text |Cite
|
Sign up to set email alerts
|

Ganglion impar block in patients with chronic coccydynia

Abstract: Introduction:Coccydynia refers to pain in the terminal segment of the spinecaused by abnormal sitting and standing posture. Coccydynia is usually managed conservatively, however in nonresponsive patients, ganglion impar block is used as a good alternate modality for pain relief. This article studies the effect of ganglion impar block in coccydynia patients who were not relieved by conservative management.Materials and Methods:The study was carried out at the pain clinic in the departments of Physical Medicine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
24
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 9 publications
4
24
0
8
Order By: Relevance
“…24 In our study, a reduction in pain beginning at 1 hour and sustained for up to 6 months was provided by the GIB in both groups. This is consistent with the study by Gonnade et al 6 which reported a dramatic relief in pain starting at 1 hour after GIB and continuing for up to 6 months in 31 patients with chronic coccygodynia resistant to conservative treatment. Our study is different from theirs in terms of being retrospective and not assessing disability.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…24 In our study, a reduction in pain beginning at 1 hour and sustained for up to 6 months was provided by the GIB in both groups. This is consistent with the study by Gonnade et al 6 which reported a dramatic relief in pain starting at 1 hour after GIB and continuing for up to 6 months in 31 patients with chronic coccygodynia resistant to conservative treatment. Our study is different from theirs in terms of being retrospective and not assessing disability.…”
Section: Discussionsupporting
confidence: 93%
“…4 In recent years, trials suggest that ganglion impar block (GIB) can be used as a treatment option for chronic refractory coccygodynia and pelvic pain, including pain caused by malignant neoplasms. [5][6][7][8][9] The most important advantages of this technique are that it can be implemented at a wide range of ages, from adolescent to elderly patients, can improve quality of life, can provide an opportunity to apply recurrent injections in patients with partial pain relief, and can provide additional beneficial effect. 8,[10][11][12] Unfortunately, an acceptable symptomatic improvement cannot be achieved in approximately 18-25% of patients treated with GIB.…”
Section: Introductionmentioning
confidence: 99%
“…In one of these studies carried out by Gunduz et al [9], a retrospective pilot study encompassing 22 chronic coccydynia patients on whom ganglion impar blockade was conducted via the transsacrococcygeal pathway, it was reported that there was a success rate of 82% after the first injection and relief from pain lasting, on average, for 6 months. In another recent study, Gonnade et al [20] prospectively examined 31 patients with chronic coccydynia on whom ganglion impar blockade had been carried out, and they evaluated their pain through the NRS and their functionality through the oswestry disability index (ODI) at 2, 4, 12, and 24 weeks [21]. The authors have reported a profound decrease in pain levels, a decrease in NRS scores, and noticeable positive results in the ODI [20].…”
Section: Discussionmentioning
confidence: 99%
“…In another recent study, Gonnade et al [20] prospectively examined 31 patients with chronic coccydynia on whom ganglion impar blockade had been carried out, and they evaluated their pain through the NRS and their functionality through the oswestry disability index (ODI) at 2, 4, 12, and 24 weeks [21]. The authors have reported a profound decrease in pain levels, a decrease in NRS scores, and noticeable positive results in the ODI [20]. Our study, in nature, supports the results of both studies, where additional steroids were administered in conjunction with local anesthetics for the purpose of ganglion impar blockade.…”
Section: Discussionmentioning
confidence: 99%
“…We praise your journal and authors Gonnade et al , on the excellent recent publication titled, “Ganglion impar block in patients with chronic coccydynia.”[1] Their study of patients with chronic coccydynia (coccyx pain) showed that ganglion impar injections with local anesthetic block and corticosteroid significantly decreased pain and disability scores even at the maximum length of study follow-up, which was 6-month postinjection.…”
mentioning
confidence: 99%